Photocatalytic Removal Of Phenol And Basic Blue 3 (BB3) Using ZnoC3N4 Under Outdoor Light Irradiation - Md. Rosli, Noor Izzati (2016)
Environmental pollution has become a major problem especially for developing countries. Water contamination by various kinds of hazardous substances might give negative impacts to the environment. Advanced Oxidation Processes (AOP) are known to have the ability to treat the contaminated water before being discharged. Among them, heterogeneous photocatalysis by ZnO catalyst have attracted recent years. However, the major problem suffers by ZnO is a high recombination rate of e-/h+ pairs which can decrease the photocatalytic degradation. Thus, coupling of ZnO with small band gap value of C3N4 can prevent these recombination of e-/h+ pairs. Therefore, in this study ZnO/C3N4 catalyst with various C3N4 weight percentage (0.7-4.9 wt%) were successfully prepared by simple impregnation method. The objectives of this study are to synthesize and characterize the ZnO/C3N4 catalyst, to evaluate the effect of process parameters on photocatalytic degradation phenol and basic blue 3 (BB3), to determine the mineralization of pollutants under the best condition, and to validate the kinetic process of photodegradation of pollutants under the best condition. For the prepared samples; X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), High Resolution Transmission Electron Microscopy (HRTEM), and UV-vis Diffuse Reflectance Spectra (UV-vis DRS) have been used for characterization. XRD result showed that the addition of C3N4 in catalyst preparation gave no peak corresponding to C3N4 possibly because of the amount C3N4 was very low. SEM result revealed that the catalyst surface was less affected by C3N4 loading. However, HRTEM images showed that the intimate contact between ZnO and C3N4 was indeed formed and it is advantageous for the photocatalytic degradation. Then, the photocatalytic activity of pure ZnO and as-prepared catalyst were evaluated for the degradation of phenol and BB3. Three process variables were studied; effect of catalyst loading, effect of catalyst loading and effect of solution pH for both phenol and BB3. The result showed that all the ZnO/C3N4 catalysts prepared catalyst exhibited better activity compared to pure ZnO especially with 3.5 wt% ZnO/C3N4 catalyst which showed highest removal percentages. The optimum catalyst loading was found at 1 g/L and 0.5 g/L for phenol and BB3, respectively. Besides, both pollutants showed the highest removal percentage at the initial concentration of 5 mg/L with the percentages of 99.4% and 89.6% for phenol and BB3, respectively. Degradation of phenol was found favor at pH 5.7 (99.4%) while for BB3 at pH 7(96.7%). At the best condition above, the TOC analysis revealed that only 56.5% and 63.6% of TOC removal for phenol and BB3, respectively. Kinetic degradation of phenol and BB3 also has been studied. The result showed that the reaction kinetic for both pollutants obeyed Langmuir-Hinshelwood (L-H) kinetic model. Finally, 3.5 wt% ZnO/C3N4 catalyst also has good repeatability and good separation ability suggested its potential application in wastewater treatment.